Chemical probe as specific detector of porcine protein or peptide in meat and meat-based products: potential applications, challenges, and the way forward - Hamsar, Mohd Nurhadi; Sazili, Awis Qurni; Md Tohid, Siti Farah (Elsevier B.V., 2024)
This review discusses the potential use of chemical probes for detecting porcine protein/peptide in meat and meat-based products. Porcine protein/peptide detection is important for religious, cultural, and food safety reasons. Chemical probe has emerged as a potential tool for the sensitive and specific detection of various proteins. This review provides an overview of different types of chemical probes, their advantages, and limitations. The current and potential applications of chemical probes in the food industry are also discussed, along with the challenges that must be addressed for their effective use. The article concludes by emphasizing the importance of chemical probes as a valuable tool for porcine protein/peptide detection and the need for further research and development to advance their use.